Concrete industrial ground floors - Neal, Frank R. (ICE design and practice guides., 2002)
The quality of floor surfaces in industrial and commercial premises can be vitally important to effective business operations. Smooth floors are particularly important for storage operations, but strength, durability and economy are demands imposed by all industrial applications. Increasingly rigorous specifications for industrial floors have resulted in considerable changes in the methods used for their construction.